Key role of adsorption site abundance in the direct electrochemical co-detection of estradiol and dopamine - Delmo, Naela; Pande, Ishan; Peltola, Emilia (Springer, 2025)
Estradiol (E2) is a hormone that influences various aspects of women's health. Beyond its reproductive functions, E2 impacts neurotransmitter systems such as dopamine (DA). Vertically aligned carbon nanofibers (VACNFs) have shown good sensitivity, selectivity against ascorbic acid (AA) and uric acid (UA), biocompatibility, and reduced fouling in DA sensing. In this study, we explore the use of Ti-Ni-CNF electrodes with CNFs grown for 5 min and 30 min for the direct electrochemical co-detection of E2 and DA. The longer growth time led to a 142% increase in average CNF length and a 36% larger electroactive surface area. In E2 detection, the electrodes demonstrate a wide linear range of 0.05-10 µM and sensitivity of 0.016 and 0.020 µA/µM for Ti-Ni-CNF-5 min and Ti-Ni-CNF-30 min, respectively. The sensor performance remains largely unaffected even in the presence of other steroid hormones such as progesterone and testosterone. Co-detection of equimolar E2 and DA shows promising peak separation of 0.34 ± 0.01 V and repeatability after 10 measurements. A notable improvement in the E2/DA peak current ratio, from 0.53 ± 0.07 to 0.81 ± 0.16, was achieved with the increased CNF length. Our results demonstrate the influence of adsorption sites in electrochemical detection, especially for analytes such as E2 and DA that both rely on adsorption for oxidation. While detecting small and fluctuating physiological concentrations remains a challenge, these findings can be used in choosing and fabricating electrode materials for more accurate and accessible continuous hormone measurements, including the possibility of multianalyte sensing platforms.